Amiodarone and Risk of Death in Contemporary Patients with Atrial Fibrillation: Findings from the TREAT-AF Study - Ullal, Aditya J. (Am Heart J, 2015)
BACKGROUND: There are limited data on mortality outcomes associated with use of amiodarone in atrial fibrillation and flutter (AF). METHODS: We evaluated the association of amiodarone use with mortality in patients with newly-diagnosed AF using complete data from the Department of Veterans Affairs (VA) national health care system. We included patients seen in an outpatient setting within 90 days of a new diagnosis for non-valvular AF between VA fiscal years 2004–2008. Multivariate and propensity-matched Cox proportional hazards were used to evaluate the association of amiodarone use to death. RESULTS: Of 122,465 patients (353,168 person-years of follow-up; age 72.1±10.3 years; 98.4% males), amiodarone was prescribed in 11,655 (9.5%). Cumulative, unadjusted mortality rates were higher for amiodarone recipients than for non-recipients (87 vs. 73 per 1000 person-years, P<0.001). However, in multivariate and propensity matched survival analysis, there was no significant difference in mortality (multivariate HR: 1.01, 95%CI: 0.97–1.05, P=0.51; propensity-matched HR: 1.02, 95%CI: 0.97–1.07, P=0.45). The hazard of death was not modified by age, sex, heart failure, kidney function, beta blocker use, or warfarin use but there was evidence of effect modification among patients diagnosed with AF as an inpatient versus outpatient. CONCLUSION: In a national health care system population of newly-diagnosed AF, overall use of amiodarone as an early treatment strategy was not associated with mortality.